2013
DOI: 10.1038/srep02686
|View full text |Cite
|
Sign up to set email alerts
|

Viking and Early Middle Ages Northern Scandinavian Textiles Proven to be made with Hemp

Abstract: Nowadays most plant textiles used for clothing and household are made of cotton and viscose. Before the 19th century however, plant textiles were mainly made from locally available raw materials, in Scandinavia these were: nettle, hemp and flax. It is generally believed that in Viking and early Middle Ages Scandinavia hemp was used only for coarse textiles (i.e. rope and sailcloth). Here we present an investigation of 10 Scandinavian plant fibre textiles from the Viking and Early Middle Ages, believed to be lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 16 publications
(17 reference statements)
0
30
0
Order By: Relevance
“…We have found that the modified Herzog test can be applied to degraded, archaeological material from the Scandinavian Viking Age (Skoglund et al . ; Lukešová et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…We have found that the modified Herzog test can be applied to degraded, archaeological material from the Scandinavian Viking Age (Skoglund et al . ; Lukešová et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Medical Cannabis, or more precisely medical marihuana, was already cultivated and used in the ancient times, due to its pharmaceutical properties and intoxicating effects [94,95,96]. However, medical marihuana, known for its high amounts of tetra hydro cannabinol, which is responsible for the intoxicating effect and the socalled "high-feeling", was prohibited by the Us Comprehensive Drug Abuse Prevention and Control Act of 1970 in the United States of America [94].…”
Section: Medical Use Of Cannabismentioning
confidence: 99%
“…Industrial hemp (Cannabis sativa L.), which has a tetrahydrocannabinol (THC) content <0.3%, is a fibre crop historically used for textiles [1], and is currently considered a renewable resource for the provision of fibres substituting synthetic ones in composites [2,3]. Besides the application-oriented aspects of this crop, hemp is an interesting model to study questions related to lignification and the development of cellulose-rich (i.e., gelatinous) secondary cell walls (SCWs).…”
Section: Introductionmentioning
confidence: 99%